Viral evolution sustains a dengue outbreak of enhanced severity - Catherine Inizan; Marine Minier; Matthieu Prot; Olivia O’Connor; Carole Forfait; Sylvie Laumond; Ingrid Marois; Antoine Biron; Ann-Claire Gourinat; Marie-Amélie Goujart; Elodie Descloux; Anavaj Sakuntabhai; et al. (Emerging Microbes and Infections)
Compared to the previous 2013–2014 outbreak, dengue 2016–2017 outbreak in New Caledonia was characterized by an increased number of severe forms associated with hepatic presentations. In this study, we assessed the virological factors associated with this enhanced severity. Whole-genome sequences were retrieved from dengue virus (DENV)-1 strains collected in 2013–2014 and from severe and non-severe patients in 2016–2017. Fitness, hepatic tropism and cytopathogenicity of DENV 2016–2017 strains were compared to those of 2013–2014 strains using replication kinetics in the human hepatic cell line HuH7. Whole-genome sequencing identified four amino acid substitutions specific to 2016–2017 strains and absent from 2013–2014 strains. Three of these mutations occurred in predicted T cell epitopes, among which one was also a B cell epitope. Strains retrieved from severe forms did not exhibit specific genetic features. DENV strains from 2016–2017 exhibited a trend towards reduced replicative fitness and cytopathogenicity in vitro compared to strains from 2013–2014. Overall, the 2016–2017 dengue outbreak in New Caledonia was associated with a viral genetic evolution which had limited impact on DENV hepatic tropism and cytopathogenicity. These mutations, however, may have modified DENV strains antigenicity, altering the anti-DENV immune response in some patients, in turn favoring the development of severe forms.Trial registration: ClinicalTrials.gov identifier: NCT04615364.